2009
DOI: 10.1016/j.jcrs.2008.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spherical aberration on visual function under photopic and mesopic conditions after cataract surgery

Abstract: Postoperative spherical aberration had a significant effect on visual function under photopic and mesopic conditions. This result indicates that reduced postoperative spherical aberration improves postoperative visual function under photopic and mesopic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 35 publications
(48 reference statements)
1
27
0
2
Order By: Relevance
“…Discussion of the pros and cons becomes questionable in light of the fact that pupil size normally decreases with age. 35 Yamaguchi et al 36 found a mean mesopic pupil size of 3.60 G 0.57 mm and a mean photopic size of 2.9 G 0.50 mm in a pseudophakic population with a mean age of 68 G 9.6 years. Age-related cataract remains the main indication for cataract surgery; hence, the practical benefits of aspheric IOLs are debatable.…”
Section: Discussionmentioning
confidence: 96%
“…Discussion of the pros and cons becomes questionable in light of the fact that pupil size normally decreases with age. 35 Yamaguchi et al 36 found a mean mesopic pupil size of 3.60 G 0.57 mm and a mean photopic size of 2.9 G 0.50 mm in a pseudophakic population with a mean age of 68 G 9.6 years. Age-related cataract remains the main indication for cataract surgery; hence, the practical benefits of aspheric IOLs are debatable.…”
Section: Discussionmentioning
confidence: 96%
“…22 Recently, Yamaguchi et al 23 found a mean mesopic pupil size of 3.60 G 0.57 mm and a mean photopic size of 2.9 G 0.50 mm in CDVA Z corrected distance visual acuity; DCNVA Z distance-corrected near visual acuity; IOL Z intraocular lens *One-way analysis of variance † Derived from the difference between the maximum and minimum value on the aberrometer refraction map (software version 3.1) z Statistically significant a pseudophakic population with a mean age of 68 G 9.6 years. Age-related cataract remains the main indication for cataract surgery; hence, the benefits of aspheric IOLs should be carefully balanced against their potential disadvantages because a reduction in spherical aberration and vertical coma may affect the depth of focus.…”
Section: Discussionmentioning
confidence: 98%
“…The latter may be because the spherical aberration was not fully corrected; this is supported by the fact that postoperative visual function has been reported as being negatively correlated with spherical aberration under natural pupil diameter conditions. 37 Decreased depth of focus may be an issue with aspheric IOLs, and it remains to be seen whether corneal spherical aberration should be fully, partially, or neutrally corrected to obtain the maximum visual benefit. 17 The photorefractor in our study has been reported using the "dynamic scan" for pupil size and accommodation, and the mean intraindividual variation was less than 0.12 D for accommodation data.…”
Section: Discussionmentioning
confidence: 99%